Folding, thrusting and development of push-up structures during the Miocene tectonic inversion of the Austral Basin, Southern Patagonian Andes (50°S) - Zerfass, Henrique (2017)
Rift and post-rift sections of the Austral Basin in the Southern Patagonian fold and thrust belt were examined in outcrop and in 2D seismic reflection sections to evaluate geometric and kinematic aspects of the extension and subsequent inversion. The syn-rift section is composed of dacitic lava flows of the El Quemado Complex (Jurassic), the lowermost unit of the basin. The coastal sandstones of the Springhill Formation (Tithonian-Berriasian) and marine shales of the Río Mayer Formation (Berriasian-Albian) are thought to be sag units. However, field data suggest that these units are also part of the syn-rift successions, as evidenced by extensional growth strata in the lower levels of the Río Mayer Formation. A dacitic flow that is texturally and compositionally similar to those of the syn-rift phase and that is termed here the Río Guanaco dacite is interfingered with the basal strata of the Río Mayer Formation and has a U-Pb zircon crystallization age of c. 141 Ma (Berriasian). The outcropping section was inverted by compression in the early Miocene, according to structural and isotopic data of adjacent areas, producing a broad anticline with inverted and fossil extensional faults as well as newly generated thrusts. At the seismic scale, most of the extensional master faults present negligible reverse slip, and shortening was accommodated in hanging wall push-up structures. This situation is interpreted as a result of the competent metamorphic basement and volcanic syn-rift section, inducing frictional lock-up of the master faults.